TOWARDS AN INNOVATIVE SOCIETY: THE STRATEGIC ROLE OF THE CREATIVE ECONOM (British Journal of Global Ecology and Sustainable Development, 2026)
The article analyzes the strategic role of the creative economy in the process of forming an innovative society from a scientific-theoretical and practical point of view. The study highlights the essence of the creative economy, its significance in economic growth, the development of human capital, increasing competitiveness, and ensuring sustainable development. Mechanisms for supporting innovative activity, institutional factors for the development of the creative industry, and priorities of state policy will also be considered. The results of the work serve to develop scientific and practical recommendations for improving the strategy of innovative development, the effective use of creative potential, and the modernization of the modern economic system.